2019
DOI: 10.26650/ase2019522326
|View full text |Cite
|
Sign up to set email alerts
|

Zooplankton Biodiversity in Reservoirs of Different Geographical Regions of Turkey: Composition and Distribution Related with Some Environmental Conditions

Abstract: The zooplankton fauna and the relationship with their environmental variables were investigated on the epilimnion layer of the seven reservoirs (Demirdöven, Devegeçidi, Menzelet, Sır, Ömerli, Porsuk, Tahtalı) of different regions (Marmara, Aegean, Mediterranean, Central Anatolia, Eastern Anatolia, Southeastern Anatolia) throughout the summer months (2015) in Turkey. According to the trophic conditions reservoirs varied between oligo-and eutrophic status. Chlorophylla concentration, measured for the estimation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 31 publications
1
11
0
Order By: Relevance
“…The similar results were obtained by Negreiros et al (2010) in Sapucai River; Saygı et al (2011) in Liman Lake; İsmail and Adnan (2016) in Harapan and Aman Lakes; and lastly Dorak et al (2019) in several reservoirs in Turkey.…”
Section: Discussionsupporting
confidence: 83%
“…The similar results were obtained by Negreiros et al (2010) in Sapucai River; Saygı et al (2011) in Liman Lake; İsmail and Adnan (2016) in Harapan and Aman Lakes; and lastly Dorak et al (2019) in several reservoirs in Turkey.…”
Section: Discussionsupporting
confidence: 83%
“…Among these reservoirs only the Büyükçekmece Reservoir is a natural water basin. Although limnological research was carried out for most of these reservoirs, the studies on the zooplankton fauna were only conducted for the Ömerli Reservoir (Kaplan, 1989;Altınyurt, 2006;Tarkan, 2010;Dorak et al, 2019) and the Büyükçekmece Reservoir (Aktan et al, 2006).…”
Section: Resultsmentioning
confidence: 99%
“…In another study carried out at the same reservoir in 2010 the results also showed eutrophic characteristics (Tarkan, 2010). However, in a recent study conducted in 2019 the physicochemical characteristics of the Ömerli Reservoir were as follows; the average temperature: 26.2 ºC, dissolved oxygen: 8.6 mg L -1 , pH: 8.5, conductivity: 320.4 μS cm -1 , transparency: 2 m, total phosphorous: 15.0 µg L -1 and chlorophyll a concentration: 11.1 µg L -1 and it was concluded that reservoir was in mesotrophic conditions (Dorak et al, 2019). 14 rotifer species found in this study were also detected at the Ömerli Reservoir namely A.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…There are some studies in various reservoirs in Turkey related in particular Rotifera. (Kaya and Altındağ, 2007;Bozkurt and Sagat, 2008;Buyurgan et al, 2010;Ayvaz et al, 2011;Yıldız, 2012;Saler and Alış, 2014;Tuna and Ustaoğlu, 2016;Saler et al, 2017;Güher and Çolak 2015;Dorak et al, 2019;Dorak, 2019;Güher, 2019). However, the distribution and diversity of Rotifera of Kayalıköy reservoir has not been studied so far.…”
Section: Introductionmentioning
confidence: 99%